Peran Kepala Desa dalam Mewujudkan Pembangunan Desa yang Berkelanjutan: Sebuah Studi Literatur Kasus-kasus di Indonesia - Rinto Z.W. Abidjulu; Feliks Arfid Guampe; Join Hengkeng (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The purpose of this study is to analyze the important role of village heads in achieving sustainable village development in Indonesia. The study employs a qualitative research approach, utilizing a literature review method to explore and synthesize various studies, articles, journals, and reports related to the village heads' roles. The data collection was conducted through a systematic literature search using relevant keywords such as "village head role," "sustainable village development," "community participation," "local resource management," "village-owned enterprises (BUMDes)," and "SDGs in villages." The gathered data were then analyzed using thematic analysis to identify key themes related to the village heads' roles in managing development, encouraging community participation, and implementing sustainable development policies. The study concludes that village heads play a multifaceted role in planning and managing village development, facilitating community participation, and ensuring transparent and accountable management of village funds. However, challenges remain, particularly in terms of corruption risks and equitable community participation. The findings emphasize the need for improved capacity building for village heads and stronger support from the government to achieve sustainable development goals at the village level.